Interfacing RuO2 with Pt to induce efficient charge transfer from Pt to RuO2 for highly efficient and stable oxygen evolution in acidic media - Kwon, Taehyun; Yang, Heesu; Jun, Minki; Kim, Taekyung; Joo, Jinwhan; Kim, Jun; Baik, Hionsuck; Kim, Jin Young; Lee, Kwangyeol (ROYAL SOC CHEMISTRY, 2021)
The oxygen evolution reaction (OER) requires a large overpotential which undermines the stability of electrocatalysts, typically IrOx or RuOx. RuOx is particularly vulnerable to high overpotential in acidic media, due to the formation of soluble species, thus making it nearly impossible to be used as a commercially viable OER electrocatalyst. Herein, we demonstrate that the charge transfer from Pt to conjoined RuO2 dramatically stabilizes the RuO2 phase against overoxidation, the main culprit of disintegration of RuO2. In this work, we compared the OER performance of three different types of Au@Pt@RuOx nanowires, namely, hetero-interfaced, gradient-alloy, and conformal-shell type, with varying degrees of interaction between Pt and RuO2. Among the studied samples, the hetero-interfaced type exhibited the highest OER mass activity of 1.311 A mg(Ru)(-1) at 1.48 V-RHE and maintained its activity durably, thus demonstrating the effectiveness of charge transfer from Pt to RuO2 in the hetero-interfaced structure against overoxidation of RuO2.
Keywords: WATER; PLATINUM; DISSOLUTION; OXIDES; ELECTROCATALYST; CHALLENGES; MORPHOLOGY; OXIDATION; TRENDS; LINES